Hubungan Status Gizi dengan Kejadian Pre Menstrual Sindrom pada Mahasiswa Kebidanan : Hubungan Status Gizi dengan Kejadian Pre Menstrual Sindrom pada Mahasiswa Kebidanan - Desi Pramita Sari; Siti Husaidah (Ahmar Metastasis Health Journal, 2021)
Introduction: Premenstrual Syndrome (PMS) is a group of symptoms that arise due to hormonal changes that occur in a woman's body before menstruation. Symptoms are felt in the form of one or more complaints both physical, psychological and emotional such as headaches, stomach cramps, constipation or diarrhea, back and waist pain, fatigue, breast pain, the onset of acne sleep disorders, joints or muscle weakness, swelling in the legs, which can interfere with productivity. This study aims to determine the relationship between nutritional status and the incidence of Pre Menstrual Syndrome among students of the Midwifery’s Study Program at Mitra Bunda’s Health Institute. Methods:The used method in this study is the Cross Sectional design, a sample used by Midwifery students with Premenstrual Syndrome, amounting to 83 respondents. Data collection in this study was in the form of a questionnaire. The analysis used in this study is univariate and bivariate analysis. Results: The results showed a relationship between nutritional status variables (p value = 0.010) with the incidence of Pre Menstrual Syndrome. Conclusion: It is expected that women especially teenagers to maintain and pay attention to nutritional status, this is intended to reduce complaints of pre menstrual syndrome. Pendahuluan: Premenstrual Syndrome (PMS) adalah sekumpulan gejala yang muncul akibat perubahan hormonal yang terjadi pada tubuh wanita sebelum menstruasi. Gejala yang dirasakan berupa satu atau lebih keluhan baik fisik, psikis maupun emosional seperti sakit kepala, kram perut, sembelit atau diare, nyeri punggung dan pinggang, kelelahan, nyeri payudara, timbulnya gangguan tidur berjerawat, kelemahan sendi atau otot, bengkak di kaki, yang dapat mengganggu produktivitas. Penelitian ini bertujuan untuk mengetahui hubungan antara status gizi dengan kejadian Pre Menstrual Syndrome pada mahasiswa Program Studi Kebidanan Institut Kesehatan Mitra Bunda. Metode: Metode yang digunakan dalam penelitian ini adalah desain Cross Sectional, sampel yang digunakan oleh mahasiswa Kebidanan Premenstrual Syndrome yang berjumlah 83 responden. Pengumpulan data dalam penelitian ini berupa kuesioner. Analisis yang digunakan dalam penelitian ini adalah analisis univariat dan bivariat. Hasil: Hasil penelitian menunjukkan adanya hubungan antara variabel status gizi (p value = 0,010) dengan kejadian Pre Menstrual Syndrome. Kesimpulan: Diharapkan wanita khususnya remaja untuk menjaga dan memperhatikan status gizinya, hal ini dimaksudkan untuk mengurangi keluhan sindroma pra menstruasi.